Tackling Corruption in Indonesia: Lessons Learned and Future Directions - Muh Ilham (Journal of Public Representative and Society Provision, 2022)
Corruption has been a longstanding issue in Indonesia, with negative consequences for economic growth, social welfare, and democratic governance. This paper aims to provide an overview of the current state of corruption in Indonesia, as well as lessons learned from previous anti-corruption efforts and future directions for tackling corruption. Through a review of the literature, the paper finds that corruption remains a pervasive problem in Indonesia, with the country ranking 102 out of 180 countries on the Corruption Perceptions Index 2020. The paper also highlights that previous anti-corruption efforts have been insufficient in addressing the root causes of corruption, which include weak governance institutions, lack of transparency and accountability, and inadequate enforcement of anti-corruption laws. In terms of future directions, the paper suggests a multi-pronged approach that includes strengthening anti-corruption institutions, addressing underlying drivers of corruption, engaging civil society, and promoting ethical leadership. The paper also emphasizes the importance of sustained political will and leadership for the success of anti-corruption efforts. Overall, this paper provides insights into the challenges and opportunities for tackling corruption in Indonesia, which is critical for promoting economic development, social welfare, and democratic governance.